2017
DOI: 10.1007/s40069-017-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Test of Concrete Specimens Subjected to Different Loading Geometries: Review and New Insights

Abstract: The objective of this work was finding out the most advisable testing conditions for an effective and robust characterization of the tensile strength (TS) of concrete disks. The independent variables were the loading geometry, the angle subtended by the contact area, disk diameter and thickness, maximum aggregate size, and the sample compression strength (CS). The effect of the independent variables was studied in a three groups of experiments using a factorial design with two levels and four factors. The like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 54 publications
4
19
0
1
Order By: Relevance
“…In all the simulations performed, it was verified that the predominant Griffith's failure condition is 3σ θ + σ r < 0, which is in agreement with the results obtained by other researchers [36,37]. Consequently, the tensile strength has been determined with the Griffith equivalent stress (11).…”
Section: New Analytical Expression For the Brazilian Test With Loadinsupporting
confidence: 87%
See 1 more Smart Citation
“…In all the simulations performed, it was verified that the predominant Griffith's failure condition is 3σ θ + σ r < 0, which is in agreement with the results obtained by other researchers [36,37]. Consequently, the tensile strength has been determined with the Griffith equivalent stress (11).…”
Section: New Analytical Expression For the Brazilian Test With Loadinsupporting
confidence: 87%
“…Failure begins when the equivalent Griffith stress σ G is greater than or equal to the tensile strength σ t of the brittle material. e work performed by Satoh [36], and verified later by others authors [20,37], concludes that the predominant failure condition in this alternative test according to the Griffith criterion is 3σ θ + σ r < 0. erefore, the tensile strength is given by the equivalent Griffith's stress [8]:…”
Section: New Analytical Expression For the Brazilian Test With Loadinsupporting
confidence: 57%
“…Tensile properties of the concrete material are significantly lower than the compression resistance, resulting in the structure being prone to tensile damage, and the dynamic direct tensile properties are difficult to measure directly by the test. Most researchers [1][2][3] have shown that the tensile test with Brazilian disc specimens yields the closest tensile strength value to the actual tensile value. Addition of fiber to concrete can effectively reduce cracks from rising and propagating, thus improving its strength and enhances its toughness and anti-impact properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…One can gain an idea of its impact if one considers that the use of concrete test specimens has been standardized into norms in various countries, such as UNI EN 12390-6, ASTM C-496. However, the BT is far from a universal test, and it is unknown whether a geometric configuration exists that favors effective, robust testing that is less sensitive to other experimental parameters [50].…”
Section: Characterization Of the Tensile Strengthmentioning
confidence: 99%